Complexity-Reduced MLD Based on QR Decomposition in OFDM MIMO Multiplexing with Frequency Domain Spreading and Code Multiplexing. (22nd August 2010) - Nagatomi Nagatomi, Kouji Kouji; Kawai Kawai, Hiroyuki Hiroyuki; Higuchi Higuchi, Kenichi Kenichi
Abstract : This paper presents a new maximum likelihood detection- (MLD-) based signal detection method for orthogonal frequency division multiplexing (OFDM) multiple-input multiple-output (MIMO) multiplexing with frequency domain spreading and code multiplexing. The proposed MLD reduces the computational complexity by utilizing signal orthogonalization based on QR decomposition of the product of the channel and spreading code matrices in the frequency domain. Simulation results show that when the spreading factor and number of code multiplexed symbols are 16, the proposed MLD reduces the average received signal energy per bit-to-noise spectrum density ratio ( E b / N 0 ) for the average packet error rate (PER) of 10 −2 by approximately 12 dB compared to the conventional minimum mean-squared error- (MMSE-) based filtering for 4-by-4 MIMO multiplexing (16QAM with the rate-3/4 Turbo code is assumed).